1998
DOI: 10.1152/ajprenal.1998.275.4.f550
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization, and gene organization of K-Cl cotransporter from pig and human kidney andC. elegans

Abstract: We isolated and characterized the cDNAs for the human, pig, and Caenorhabditis elegansK-Cl cotransporters. The pig and human homologs are 94% identical and contain 1,085 and 1,086 amino acids, respectively. The deduced protein of the C. elegans K-Cl cotransporter clone (CE-KCC1) contains 1,003 amino acids. The mammalian K-Cl cotransporters share ∼45% similarity with CE-KCC1. Hydropathy analyses of the three clones indicate typical KCC topology patterns with 12 transmembrane segments, large extracellular loops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 32 publications
9
73
2
Order By: Relevance
“…While staurosporine can induce apoptosis only at high concentrations, at lower concentrations it has been shown to inhibit the protein kinases PKC, PKA, PKG, CAMKII, and MLCK, as well as other kinases in a concentration-dependent manner, and to stimulate K-Cl cotransport in red blood cells (25,(35)(36)(37). Because staurosporine's strongest inhibitory effect is on PKC kinases, and in C. elegans it has been shown to inhibit PKC activity (38), we tested whether it exerts its effects on regrowing neurites via the inhibition of this particular kinase.…”
Section: Resultsmentioning
confidence: 99%
“…While staurosporine can induce apoptosis only at high concentrations, at lower concentrations it has been shown to inhibit the protein kinases PKC, PKA, PKG, CAMKII, and MLCK, as well as other kinases in a concentration-dependent manner, and to stimulate K-Cl cotransport in red blood cells (25,(35)(36)(37). Because staurosporine's strongest inhibitory effect is on PKC kinases, and in C. elegans it has been shown to inhibit PKC activity (38), we tested whether it exerts its effects on regrowing neurites via the inhibition of this particular kinase.…”
Section: Resultsmentioning
confidence: 99%
“…This alkaloid acts as a kinase inhibitor that activates KCCs (33,60). Staurosporine closely mimicked the effect of NEM.…”
mentioning
confidence: 80%
“…In addition, each mKCC1 truncation mutant examined in the current work can be covalently cross-linked to the homodimeric state. 6 Thus, the presence of neither cytoplasmic domain of mKCC1 is required for homo-oligomerization.…”
Section: Figmentioning
confidence: 99%
“…Even in isotonic conditions, 86 Rb ϩ influx was higher in oocytes expressing mKCC1 than in water-injected oocytes (p Ͻ 0.001). Our previous studies of mKCC1 in Xenopus oocytes (7) and other studies of rabbit (5,19) and human KCC1 in 293 cells (6) and of native Xenopus oocyte K-Cl cotransport (14) have shown that this activated 86 Rb ϩ influx requires bath chloride and is inhibited by the serine-threonine phosphatase inhibitors okadaic acid and calyculin and by the diuretic diindenylalkanoic acid. Removal of only the eight C-terminal residues from the C-terminal cytoplasmic tail of mKCC1, as in ⌬ c 1077, preserved a low level of activity in isotonic medium (p ϭ 0.008) but abolished stimulation of 86 Rb uptake elicited by hypotonicity.…”
Section: C-terminal Truncation Of Mkcc1 Leads To Loss Of Function-mkcmentioning
confidence: 99%
See 1 more Smart Citation